The Influence of Industrial Steel Waste on Slump Test and Compressive Strength in Eco-Friendly Concrete Fabrication - Vijayasree, Vijaya Prakash; Wan Lutfi Wan Johari, (International Journal of Sustainable Construction Engineering and Technology, 2022)
This study evaluated the suitable percentage of replacing natural coarse aggregate (crushed granite) with wasted Zinc Aluminum (Zincalume) generated from metal roofing fabrication industry to produce G35 grade eco–friendly concrete. Design mix for the wasted Zincalume substitution with crushed granite was prepared at 10%, 15% and 20% where the control mix specimen used as reference for mechanical strengths comparison. The mechanical strengths were observed with the increasing of curing age, but the strengths reduced with the increment of wasted Zincalume in the mixture. An amount of 10% of Zincalume substitution gave the optimum mechanical strength values. Acid – base reaction between cement and Zincalume coating in the concrete mixture, generated hydrogen gas, which reduced the compressive strength. The higher percentage of Zincalume in the concrete mixture, the weaker mechanical strengths were obtained. By recycling the steel waste, the eco – friendly concrete encourages to protect environment and enhance the economy growth.